2014
DOI: 10.1080/15428052.2014.904834
|View full text |Cite
|
Sign up to set email alerts
|

How Often Do We Use Cooking Utensils? An Exploratory Study

Abstract: This study examined the use of cooking utensils among Australians and the influence of respondents' socio-economic characteristics on utensil usage. A total of 1,027 Australians completed an online survey and reported frequencies of 23 utensils used and details of their demographics, cooking experiences, and household types. Latent class analysis suggested two types of usage patterns: high and moderate use. Ethnic background, cooking evening meals from scratch, and the number of people in the household associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…Also of note is that despite the greater number of higher educated people in the 2014 cohort, the findings were similar, suggesting that educational status does not play a large role in peoples’ views on this subject. These findings are backed by previous research which found a lack of association between socio-demographic variables and the use of herbs, spices and utensils, as well as interest in cooking (Wang and Worsley, 2014; Worsley, Wang, Ismail and Ridley, 2014).…”
Section: Discussionsupporting
confidence: 61%
“…Also of note is that despite the greater number of higher educated people in the 2014 cohort, the findings were similar, suggesting that educational status does not play a large role in peoples’ views on this subject. These findings are backed by previous research which found a lack of association between socio-demographic variables and the use of herbs, spices and utensils, as well as interest in cooking (Wang and Worsley, 2014; Worsley, Wang, Ismail and Ridley, 2014).…”
Section: Discussionsupporting
confidence: 61%
“…The survey questionnaire was divided into five broad sections related to (1) current cooking practices; (2) the preparation of various types of evening meals; (3) the use of ingredients and utensils; (4) food preparers' interest in learning more about evening meal preparation; and (5) background information about the age, gender and educational background of the respondents (Table ). Findings from the first and third sections will be reported elsewhere (Wang and Worsley, 2013a,b). Responses to the fourth section and part of second section are the subject of this report.…”
Section: Methodsmentioning
confidence: 58%
“…to have a meal ready for a critical family group by a certain time most evenings). We have observed similar lack of socio‐demographic associations in analyses of the use of herbs, spices and utensils, collected as part of this survey (Wang and Worsley, 2013a,b).…”
Section: Discussionmentioning
confidence: 98%
“…Metal spoons were also used by 14% of people while mixing dry ingredients, and 16% while mixing wet and dry ingredients. Spoons represent one of the most common utensils used by people in their kitchens, as reported by Wang and Worsley [ 26 ]. The use of the hands might be related to the easiness to prepare the products by direct contact with them.…”
Section: Resultsmentioning
confidence: 99%